2007
DOI: 10.1111/j.1432-2277.2007.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Ozone oxidative preconditioning is mediated by A1adenosine receptors in a rat model of liver ischemia/ reperfusion

Abstract: Summary The liver is damaged by sustained ischemia in liver transplantation, and the reperfusion after ischemia results in further functional impairment. Ozone oxidative preconditioning (OzoneOP) protected the liver against ischemia/reperfusion (I/R) injury. The aim of this study was to investigate the role of A1 adenosine receptor on the protective actions conferred by OzoneOP in hepatic I/R. By using a specific agonist and antagonist of the A1 subtype receptor (2‐chloro N6 cyclopentyladenosine, CCPA and 8‐cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 39 publications
(83 reference statements)
0
27
0
Order By: Relevance
“…However, administration of an adenosine A 1 receptor antagonist before ischemia attenuates ischemia-reperfusion injury (Magata et al, 2007;Kim et al, 2008). Ozone oxidative preconditioning is mediated by A 1 receptors in a rat model of liver ischemia-reperfusion (León Fernández et al, 2008). Selective intrarenal human A 1 receptor overexpression reduced acute liver (and kidney) injury after hepatic ischemia-reperfusion in mice (Park et al, 2010b).…”
Section: Ischemiamentioning
confidence: 99%
“…However, administration of an adenosine A 1 receptor antagonist before ischemia attenuates ischemia-reperfusion injury (Magata et al, 2007;Kim et al, 2008). Ozone oxidative preconditioning is mediated by A 1 receptors in a rat model of liver ischemia-reperfusion (León Fernández et al, 2008). Selective intrarenal human A 1 receptor overexpression reduced acute liver (and kidney) injury after hepatic ischemia-reperfusion in mice (Park et al, 2010b).…”
Section: Ischemiamentioning
confidence: 99%
“…Peralta et al [14] and others [15] have demonstrated that hepatoprotection induced by IPC is mediated by the activation of A 2 R. Although, Schauer et al [16] reported no evidence for a role of A 2 R in the cytoprotective effects of IPC, they suggested the implication of other adenosine receptor subclasses or additional mediators of IPC that could play a role in such settings. Recently, we have reported that the protective effects of oxidative preconditioning in liver are mediated by the activation of A 1 R by CCPA [17]. Moreover, experimental evidence demonstrates the involvement of A 1 R in other organs [12,13,[18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…Administration of an adenosine A 1 receptor antagonist before ischaemia attenuated ischaemia-reperfusion injury [153,169]. Oxidative preconditioning by ozone was mediated by A 1 receptors in a rat model of liver ischaemia reperfusion [163].…”
Section: Ischaemia and Vascular Injurymentioning
confidence: 94%